2019
DOI: 10.1186/s12916-019-1364-z
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and enrichment analyses of non-alcoholic fatty liver disease identify new trait-associated genes and pathways across eMERGE Network

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a common chronic liver illness with a genetically heterogeneous background that can be accompanied by considerable morbidity and attendant health care costs. The pathogenesis and progression of NAFLD is complex with many unanswered questions. We conducted genome-wide association studies (GWASs) using both adult and pediatric participants from the Electronic Medical Records and Genomics (eMERGE) Network to identify novel genetic contributors to this condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 66 publications
4
144
0
Order By: Relevance
“…13,14 To date, most adequately powered GWASs relevant to NAFLD have addressed either radiologically determined HTGC 4,6,12 or clinical biochemistry parameters such as ALT. 12,15 They have therefore been unable to address the more clinically relevant phenotypes of steatohepatitis grade or fibrosis stage (reviewed 3 ). One GWAS has assessed a large number of histologically characterised patients, reporting associations with both PNPLA3 and with chromosome 19 close to TM6SF2.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 To date, most adequately powered GWASs relevant to NAFLD have addressed either radiologically determined HTGC 4,6,12 or clinical biochemistry parameters such as ALT. 12,15 They have therefore been unable to address the more clinically relevant phenotypes of steatohepatitis grade or fibrosis stage (reviewed 3 ). One GWAS has assessed a large number of histologically characterised patients, reporting associations with both PNPLA3 and with chromosome 19 close to TM6SF2.…”
Section: Introductionmentioning
confidence: 99%
“…The same TRIB1 region was identified in a recent GWAS of NAFLD, lending further credibility to the relevance of this locus. 53 As well as providing insight into the pathobiology of alcohol-related cirrhosis, a deeper understanding of the underlying genetics could, in time, help clinicians differentiate the minority of liver disease patients at high risk of serious liver morbidity from the low-risk majority. In principle therefore, host genetic data may help to increase earlier detection of chronic liver disease in high-risk patients-thus addressing the issue of frequently delayed diagnosis of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…As said above, NAFLD implicates intricate interactions between many risk factors and genetic predisposition [ 19 ]. Several studies have suggested a genetic underpinning for NAFLD [ 20 , 21 ].…”
Section: Genetics Of Nafldmentioning
confidence: 99%